Отбор по социальному происхождению в среднюю школу и в высшие учебные заведения - Доманьский, Х. (Социология: теория, методы, маркетинг, 2005)
The article is devoted to educational inequalities in Poland viewed in a long time
frame. Educational inequalities used to be measured in the terms of effect of social
origin on the selection at the first and second thresholds of education, i.e. when moving
from primary to secondary school, and from secondary school to university. The results
of various analyses conducted so far point to the decisive role of the effect of social
origin emerging especially at the first threshold (from primary to secondary school).
Moreover, this effect seemed to be persistent for a long time. However, according to my
analyses the effect of social origin on passing the educational threshold has risen
dramatically in the 1990s and then it has fallen to the level from the time before
transformation. This analysis is based on data coming from research being carried out
on national samples from 1982 to 2002 in Poland.